2014
DOI: 10.3136/fstr.20.1121
|View full text |Cite
|
Sign up to set email alerts
|

Mouthful Size Effects on Mastication Effort of Various Hydrocolloid Gels Used as Food Models

Abstract: This study aimed to quantify effects of food mouthful size on eating effort while masticating solid foods represented by five hydrocolloid gels varying in texture by means of electromyography (EMG). Eleven subjects ate 3 (S) and 6 (L) mL mouthfuls of five gel samples in their normal way without any designated conditions. EMG activities from both masseter muscles, as jaw-closing muscles, and the suprahyoid muscles, as the jaw-opening muscles, were recorded during free eating. Differences in EMG variables were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This suggested that the volume of gel consumed at one time affects salivation only when the volume is sufficiently small; a volume over a certain threshold does not stimulate additional salivation. A previous study showed that the volume of food consumed at one time affects the number of chews and duration of mastication but not the masseter muscle activity per chew (Kohyama et al, 2014(Kohyama et al, , 2016a. Unfortunately, the number of chews and the duration of mastication could not be evaluated in this study because we set the duration of mastication to be 30 s. In fact, EMG activities in 30 s did not differ significantly between mastication of 1 piece and 3 pieces of each gel type, suggesting that the increase in salivation for mastication of ≥ 2 pieces compared with 1 piece was hardly caused by the difference in EMG activity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This suggested that the volume of gel consumed at one time affects salivation only when the volume is sufficiently small; a volume over a certain threshold does not stimulate additional salivation. A previous study showed that the volume of food consumed at one time affects the number of chews and duration of mastication but not the masseter muscle activity per chew (Kohyama et al, 2014(Kohyama et al, , 2016a. Unfortunately, the number of chews and the duration of mastication could not be evaluated in this study because we set the duration of mastication to be 30 s. In fact, EMG activities in 30 s did not differ significantly between mastication of 1 piece and 3 pieces of each gel type, suggesting that the increase in salivation for mastication of ≥ 2 pieces compared with 1 piece was hardly caused by the difference in EMG activity.…”
Section: Discussionmentioning
confidence: 95%
“…The desired volume of each solution was obtained by adding deionized water. Each solution was then poured into glass ring molds (20-mm diameter; 10-mm height; 3.14-mL volume) (Ishihara et al, 2013(Ishihara et al, , 2014Kohyama et al, 2014Kohyama et al, , 2016bKohyama et al, , 2017. The samples in molds were heated at 85 ℃ for 30 min and then refrigerated at 4 ℃ for at least 1 h. Gels were allowed to stand at 23 ℃ for 1-3 h before using for experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation